(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2020)
Complex oxide phosphates Na1.5Co1.5Fe1.5(PO4)3, Na1.75Co1.75Fe1.25(PO4)3, Na2Co2Fe(PO4)3 and Li0.25Na1.75Co2Fe(PO4)3, belonging to the alluaudite structural type (monoclinic system, space group C2/c) were synthesized by the melting method with further annealing of the homogenous glasses at a temperature 600°C. According to powder X-ray diffraction data the partial substitution of sodium cations by lithium cations in the initial phosphate matrix Na2Co2Fe(PO4)3 led to decreasing of lattice parameters for Li0.25Na1.75Co2Fe(PO4)3 (a = 11.7572(3) Å, b = 12.4528(4) Å, c = 6.4416(2) Å and β = 113.911(1)°). The FTIR-spectroscopy results confirmed the presence of PO4-tetrahedra in the composition of prepared phases. Modes in the regions of 400–600 cm-1 and 900–1000 cm–1 were assigned to symmetric and asymmetric stretching vibrations of phosphate tetrahedron in the alluaudite-type structure, respectively. The effect of partial substitution of sodium cations by lithium cations in the phosphate matrix Na2Co2Fe(PO4)3 as well as the decrease of sodium cations amounts in the alluaudite-related structure for the phases of Na1.5Co1.5Fe1.5(PO4)3 and Na1.75Co1.75Fe1.25(PO4)3 on the conductive properties of compounds were analyzed. It was found that increasing of sodium cations amount in the channels of the alluaudite-related structure leads to an increase of the specific conductivity from 0.011 Om-1m-1 for Na1.75Co1.75Fe1.25(PO4)3 to 0.15 Om–1m–1 for Na2Co2Fe(PO4)3 at a temperature of 550 °C. It was also found that partial substitution of sodium cations by lithium cations in the initial phosphate matrix Na2Co2Fe(PO4)3 no significant influence on conductivity of phase Li0.25Na1.75Co2Fe(PO4)3 (s = 0.095 Оm–1m–1 at a temperature of 550 °C). In the case of phosphates Na1.75Co1.75Fe1.25(PO4)3 and Li0,25Na1,75Co2Fe(PO4)3 decreasing of conductive properties in the temperature ranges 190–250 °С and 550–590 °С, respectively are caused by contribution of different components in general conductivity. The synthesized phases can be used in the development of materials with conductive properties.